Prevalence of Sleep Bruxism and Association with Oral Health Conditions in Schoolchildren in a Municipality in Southern Brazil - Eliane Traebert; Andréia Clara Nazário; Rodrigo Dias Nunes; Sissiane Margreiter; Keila Cristina Raush Pereira; Simone Xavier Silva Costa; Jefferson Traebert (Association of Support to Oral Health Research (APESB), 2022)
Objective: To estimate the prevalence of sleep bruxism and its association with oral health conditions in schoolchildren. Material and Methods: Cross-sectional study carried out in public schools of Tubarão, SC, Brazil with students aged 10 to 15 years. The oral examination was performed in classrooms by dental surgeons, using the WHO criteria. Data on malocclusions, caries and dental trauma, fluorosis, bleeding gums and the presence of dental calculus were collected. For the diagnosis of bruxism, the criterion of the American Academy of Sleep Medicine was adopted. The chi-square test was used to assess the association between sleep bruxism and oral health conditions. Prevalence ratios and  confidence intervals were estimated by Poisson regression with robust estimator. Results: A total of 389 students were examined. The prevalence of sleep bruxism was 22.0%. Schoolchildren with malocclusion, increased overjet and dental calculus showed a statistically higher and independent prevalence of 9.0% (p=0.003), 6.0% (p=0.006) and 19.0% (p<0.001), respectively. Conclusion: Prevalence of sleep bruxism was 22% in the study population and was associated with malocclusions, particularly increased overjet, and the presence of dental calculus.